Inhibition of the alpha-L-arabinofuranosidase III of Monilinia fructigena by 1,4-dideoxy-1,4-imino-L-threitol and 1,4-dideoxy-1,4-imino-L-arabinitol. - Axamawaty, M T (1990)
1. 1,4-Dideoxy-1,4-imino-L-threitol was synthesized and the synthesis of 1,4-dideoxy-1,4-imino-L-arabinitol was improved. 2. Both compounds are competitive inhibitors of Monilinia fructigena alpha-L-arabinofuranosidase III, the additional hydroxymethyl group in the arabinitol contributing about 17.8 kj/mol (4.25 kcal/mol) to the Gibbs free energy of binding. 3. The affinities (1/Ki) of both compounds vary with pH in a classical bell-shaped way, the pKa value being that of the acid-catalytic group on the enzyme [5.9; Selwood & Sinnott (1988) Biochem. J. 254, 899-901] and the pKb values being those of the free inhibitors, 7.6 and 7.8 respectively. 4. On the basis of these and literature data we suggest that efficient inhibition of a glycosidase at its pH optimum by an appropriate iminoalditol will be found when the pKa of the iminoalditol is below that of the acid-catalytic group of the target enzyme.